2019
DOI: 10.17645/pag.v7i1.1853
|View full text |Cite
|
Sign up to set email alerts
|

Following, Challenging, or Shaping: Can Third Countries Influence EU Energy Policy?

Abstract: Can non-EU member states influence the EU’s energy policy? The Europeanization of energy policy in third countries is often described as a one-directional process in which these countries essentially adopt the EU <em>energy acquis</em>. Our article questions this dominant view by exploring whether and how third countries can influence the formulation and implementation of EU energy policy. We argue that relative differences in third country influence depend on their access to relevant venues and ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 17 publications
(20 reference statements)
1
24
0
Order By: Relevance
“…Supranational instruments for external market governance include rules-based market multilateralism (Energy Charter Treaty), norm export through the externalisation of energy market legislation (Energy Community, EEA) and bilateralism (Energy Dialogues) (Aalto 2008;Hofmann et al 2019;Sitter 2014, 2015b).…”
Section: European External Energy Policy: Incomplete Integrationmentioning
confidence: 99%
“…Supranational instruments for external market governance include rules-based market multilateralism (Energy Charter Treaty), norm export through the externalisation of energy market legislation (Energy Community, EEA) and bilateralism (Energy Dialogues) (Aalto 2008;Hofmann et al 2019;Sitter 2014, 2015b).…”
Section: European External Energy Policy: Incomplete Integrationmentioning
confidence: 99%
“…These countries have considerable autonomy in making decisions about their own energy policy: the EU often uses these ideas and vice versa [10,11]. Depending on the involvement in the EU energy policy and the size of the energy resources, four groups of countries outside the EU can be distinguished: challengers (e.g., Russia, Turkey-high resources, no links with the EU), outsiders (e.g., Belarus-no links with the EU and low resources), shapers (commitment to EU energy policy and high resources), and followers (members of EnC and Iceland) [12].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, regarding Brexit's impact on environmental policies, Burns et al (2019) observed that Europeanisation's influence is so important that even Brexit will not lead to environmental policy reversals. In terms of third countries, Iangbein and Börzel (2013) argued that many factors affect Eastern neighbourhood countries' influence on EU policy changes, and Hofmann et al (2019) asserted that even third countries such as Switzerland and Norway can shape the EU's energy policies, because of their accession and structural power.…”
Section: The Europeanisation Process: a Theoretical Contextmentioning
confidence: 99%